2017
DOI: 10.1007/s40092-017-0225-7
|View full text |Cite
|
Sign up to set email alerts
|

Incentive mechanism based on cooperative advertising for cost information sharing in a supply chain with competing retailers

Abstract: This paper proposes a new motivation for information sharing in a decentralized channel consisting of a single manufacturer and two competing retailers. The manufacturer provides a common product to the retailers at the same wholesale price. Both retailers add their own values to the product and distribute it to consumers. Factors such as retail prices, values added to the product, and local advertising of the retailers simultaneously have effect on market demand. Each retailer has full information about the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…This dissemination is particularly crucial for sharing information about disruptions and strategies necessary for improving supply chain resilience. Setak et al (2018) contend that IT is emerging as a critical success factor for modern firms in managing potential vulnerabilities and disruptions in their supply chains. Siagian et al (2021) concluded that companies' IT can integrate the system to increase its response as a form of supply chain resilience.…”
Section: Theoretical Model and Hypothesis Developmentmentioning
confidence: 99%
“…This dissemination is particularly crucial for sharing information about disruptions and strategies necessary for improving supply chain resilience. Setak et al (2018) contend that IT is emerging as a critical success factor for modern firms in managing potential vulnerabilities and disruptions in their supply chains. Siagian et al (2021) concluded that companies' IT can integrate the system to increase its response as a form of supply chain resilience.…”
Section: Theoretical Model and Hypothesis Developmentmentioning
confidence: 99%
“…Helper et al [13] develop a decentralized decision process to show the benefits of IS to retailers under varying levels of supplier capacity and supply allocation mechanisms. Setak et al [50] study with a decentralized SC and use a cooperative advertising program for IS. Dai et al [51] investigate the relationship between IS and bullwhip effect in a decentralized SC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In supply chain, sharing the right information is very desirable and it reduces the risk in the supply chain (Nishat Faisal et al 2006). In the present dynamic and indeterminate supply chain environment, to minimize the risk in the supply chain, it is essential to form a group of active partners and right information should flow among all partners of that particular group (Setak et al 2018;Tohidi et al 2017). Information sharing also plays a vital role in minimizing the bullwhip impact (Jain et al 2017).…”
Section: It Capability/information Sharingmentioning
confidence: 99%